Light induced double 'on' state anti-ambipolar behavior and self-driven photoswitching in p-WSe2/n-SnS2 heterostructures. (12th May 2017) - Wang, Yan; Zhou, Wu-Xing; Huang, Le; Xia, Congxin; Tang, Li-Ming; Deng, Hui-Xiong; Li, Yongtao; Chen, Ke-Qiu; Li, Jingbo; Wei, Zhongming
Abstract: P–n junctions based on vertically stacked van der Waals (vdW) materials have attracted extensive attentions and may offer novel physical performances for the design of next-generation electronics. Here, vertically stacked p-WSe2 /n-SnS2 heterostructures have been fabricated by a polymethyl methacrylate (PMMA)-assisted transfer method. The unique electronical properties and self-driven photoelectric characteristics of the heterostructures are measured. The transfer current of the heterostructures show gate-tunable 'anti-ambipolar' behavior under dark condition with the maximum of the on/off ratio exceeding 10 5, while under light illumination it triggers double 'on' state anti-ambipolar behavior. The 'anti-ambipolar' behavior under dark condition and the 'on' state I under light illumination is originating from the in series of p-channel in WSe2 and n-channel in SnS2, while the 'on' state II can be attributed to the gate-controlled Schottky barrier modulation between the heterostructure and the Au electrodes. The heterostructure also shows self-driven photoswitching performance under 532 nm laser, which can be attributed to the type-II band alignment and the build-in potential of p–n heterostructure.